Mapping Mitotic Death: Functional Integration of Mitochondria, Spindle Assembly Checkpoint and Apoptosis - Ruan, Weimei; Lim, Hong Hwa; Surana, Uttam (Frontiers in Cell and Developmental Biology, 2019)
Targeting the mitotic pathways of rapidly proliferating tumour cells has been an effective strategy in traditional cancer therapy. Chemotherapeutics such as taxanes and vinca alkaloids which disrupt microtubule function have enjoyed clinical success; however, the accompanying side effects, toxicity and multi drug resistance remain as serious concerns. The emerging classes of inhibitors targeting mitotic kinases and proteasome face their own set of challenges. It is hoped that elucidation of the regulatory interface between mitotic checkpoints, mitochondria and mitotic death will aid the development of more efficacious anti-mitotic agents and improved treatment protocols. The links between the spindle assembly checkpoint (SAC) and mitochondrial dynamics that control the progression of anti-mitotic agent-induced apoptosis have been under investigation for several years and the functional integration of these various signalling networks is now beginning to emerge. In this review, we highlight current research on the regulation of SAC, the death pathway and mitochondria with particular focus on their regulatory interconnections.